The stonecutter - Läckberg, Camilla, 1974- (Pegasus Books, 2012)
When a young girl's body is pulled out of the harbor in the small Swedish resort town of Fjallbacka, Det. Patrik Hedström becomes the lead investigator as he struggles with lazy and inept colleagues and an even remoter-than-usual boss. It's his grim task to discover who could be behind the murder of the child both he and his partner Erica knew well.